Accountability Of The Indonesian National Army Member Who Commited Corruption Crime On The Housing Obligatory Savings For Army 2020 - Sara, Rineke; Prastyanto, Yanwiyatono (CV. Publikasi Indonesia, 2024)
Corruption is not only carried out by civil society, TNI members who have undergone disciplinary training can also be engaged in committing corruption, specifically undertook by Brigadier General TNI Yus Adi Kamrullah, S.E., M.Si. and Ni Putu Purnamasari who is a TNI member in the case of TNI-AD housing savings corruption in 2019-2020. The problem of this research is how to account for TNI members who engage in corrupting crimes in the 2020 Army Housing Compulsory Savings (TWP AD). The research method used is a statutory approach and a conceptual approach. The type of research used is normative, with primary, secondary and tertiary legitimate provisions. From the outcomes, it was concluded that the criminal responsibility of the perpetrator in this case was sentenced to defendant 1: Brigadier General TNI (ret.) Yus Adi Kamrullah, S.E., M.Si. Defendant-2: Ni Putu Purmasari has been legitimately and conclusively proven jointly and continuously to have committed the corruption crime. Sentencing the defendants to basic and additional crimes